Quantitative Assessment of Luliconazole and Gallic Acid Simultaneously in Formulated Emulgel by UV Spectrophotometric Methods (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: Three new UV spectrophotometric approaches specifically, simultaneous equation (SME),absorbance ratio (ASR), and first derivative (zero crossing) spectroscopic techniques were developed and validatedfor simultaneous estimation of luliconazole (LCZ) and gallic acid (GLA) in emulgel formulation which weresimple, sensitive, precise, and accurate. Materials and Methods: In SME method, absorbance was measured at299 and 259 nm for both the drugs. LCZ and GLA were estimated at 299 and 266 nm in the ASR method. Firstderivative (zero crossing) method depended on the change of UV spectra in to first derivative spectra followedby measurement of first derivative signal at 249 and 259 nm for LCZ and GLA, respectively, using 4 nm aswavelength interval (Δλ) and 4 as scaling factor. Developed methods were validated according to ICH guidelinesincluding parameters, namely, specificity, linearity, range, precision and accuracy, limit of detection, and limitof quantification. Results and Discussion: All three techniques showed direct relation of absorbance in theconcentration range of 1-30 μg/ml for both the drugs. Good repeatability, low intra and inter-day variability,indicate that precise agreement within the value. Recovery studies for both drugs ranged from 97 to 102 percent,recommending that the methods are effective. Results of method validation parameters such as linearity and range,precision, and accuracy adhere to ICH guideline acceptable limit. Conclusion: All the developed methods werefound to be quick, profoundly accurate and financially effective; and henceforth can be valuable for simultaneousestimation of LCZ and GLA in emulgel formulation for routine quality control analysis.